Dendritic nanoconjugates of photosensitizer for targeted photodynamic therapy. (15th July 2015) - Yuan, Ahu; Yang, Bing; Wu, Jinhui; Hu, Yiqiao; Ming, Xin
Graphical abstract: Abstract: Application of photodynamic therapy for treating cancers has been restrained by suboptimal delivery of photosensitizers to cancer cells. Nanoparticle (NP)-based delivery has become an important strategy to improve tumor delivery of photosensitizers; however, the success is still limited. One problem for many NPs is poor penetration into tumors, and thus the photokilling is not complete. We aimed to use chemical conjugation method to engineer small NPs for superior cancer cell uptake and tumor penetration. Thus, Chlorin e6 (Ce6) was covalently conjugated to PAMAM dendrimer (generation 7.0) that was also modified by tumor-targeting RGD peptide. With multiple Ce6 molecules in a single nanoconjugate molecule, the resultant targeted nanoconjugates showed uniform and monodispersed size distribution with a diameter of 28 nm. The singlet oxygen generation efficiency and fluorescence intensity of the nanoconjugates in aqueous media were significantly higher than free Ce6. Targeted nanoconjugates demonstrated approximately 16-fold enhancement in receptor-specific cellular delivery of Ce6 into integrin-expressing A375 cells compared to free Ce6 and thus were able to cause massive cell killing at low nanomolar concentrations under photo-irradiation. In contrast, they did not cause significant toxicity up to 2 μM in dark. Due to their small size, the targeted nanoconjugates could penetrate deeply into tumor spheroids and produced strong photo-toxicity in this 3-D tumor model. As a result of their great cellular delivery, small size, and lack of dark cytotoxicity, the nanoconjugates may provide an effective tool for targeted photodynamic therapy of solid tumors.